Sound levels produced at and in the occluded ear of the talker - ŁĘTOWSKI, T.; CARAVELLA, J. M. (Archives of Acoustics, 1994)
Sound pressure levels (SPL) generated in the ear of the talker depend on both air and bone conduction feedback paths. In the present study six talkers (three females and three males) produced six phonemes: /u/, /a/, /i/, /m/ and /v/ and three shouts "help", "fire", and "no". The SPLs generated in the occluded and at the unoccluded ear of the talker were measured. Results indicated that occluding the ear canal enhanced auditory feedback for /u/, /i/, /m/, and /v/ sounds and reduced it for /a/ and loud shouts. These findings may have implications for speech rehabilitation programs and hearing aid fitting.